SOLUBILITY OF MAGNESIUM AND ITS INTERACTION WITH IMPURITY ELEMENTS OF CAST IRON - Ju. A. Ageev; V. I. Shkurkin; S. V. Buldygin (Литьë и металлургия)
Solubility of liquid magnesium in cast irons is calculated and its significance at steam pressure of magnesium equal 1 atm is determined.